Influence of Graded AlGaN sub-channel over the DC and Breakdown characteristics of a T-gated AlGaN/GaN/AlInN MOS-HEMT. (August 2021) - Sandeep, V.; Pravin, J. Charles
Abstract: The impact of graded Al0 . 05 Ga0 . 95 N sub-channel over the DC characteristics of AlGaN/GaN/AlInN Metal Oxide Semiconductor-High Electron Mobility Transistor (MOS-HEMT) has been investigated here. By placing a field plate over the gate region and forming a T-gated structure, the breakdown characteristics are examined using Sentaurus Technology Computer-Aided Design (TCAD) simulation tool. An analytical study is carried out into the evaluation of various device parameters like drain current, transconductance and threshold voltage. RF parameters like cut-off frequency and gain has also been examined. Various physical models such as hydrodynamic, thermodynamic, piezoelectric polarization, impact ionization models are considered. HfO2 as an oxide layer directly influences the charge confinement near the Two-Dimensional Electron Gas (2DEG), thereby causing a positive shift in the threshold voltage of the device. T-gated formation of the gate helped in enhancing the breakdown voltage of the device to nearly 750 V. A maximum current drive of 1.79 A/mm mm was obtained for the proposed device, nearly 24% improvement from the conventional Composite-channel (CC) HEMT. The current outcomes and the produced frequency characteristics determines the linearity enhancement occurred in the device, caused due to the graded AlGaN sub-channel below the GaN channel layer. The trade-off between specific on-resistance and breakdown voltage is well preserved by employing a T-gated structure with low normal gate length. The outcomes prove the device to be a prime contender for high power switching as well as large signal applications. Highlights: The impact of graded AlGaN sub-channel over the DC characteristics of AlGaN/GaN/AlInN MOS-HEMT has been investigated here. HfO2 dielectric directly influences the charge confinement near 2DEG, causing a positive shift in the threshold voltage. T-gated formation of the gate helped in enhancing the breakdown voltage of the device to nearly 750 V. A 24% enhancement in current drive is observed when the device is brought in comparison with a conventional CC HEMT.